(untitled) (De Legibus - Law Journal, 2022)
After a brief analysis of the trust’s principle incidence, in horizontal and vertical division of work, this paper examines the possibility of recognizing “negligent co-perpetration” and “negligent perpetration by means”, as opposed to application of the “extensive concept of perpetrator”, to solve cases of controversial causality and of the innocent perpetrator instrumentalization. It is concluded by defending a restrictive concept of perpetrator and, therefore, by the need to operate with the categories of co-perpetration and perpetration by means also in negligent crimes.